Pengaruh Pijat Endorphine terhadap Jumlah Pengeluaran Darah pada Kala Empat Persalinan Normal Primipara di Bidan Praktek Mandiri Kabupaten Indramayu Tahun 2013 - Siti Koriah; Suryani Supardan; Bahiyatun Bahiyatun; Ari Soewondo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
Postpartum hemorrhage is bleeding more than 500 cc which occurs after the baby is born vaginally. One way to reduce the blood that comes out can be done with the Endorphin massage. Endorphin massage is performed at stage four, during which a lot of blood coming out of unknown cause. If Endorphin massage is done blood loss may be reduced. This study is aimed to determine the differences in the total amount of blood loss in the stage four of the primiparous normal deliveries between those who received Endorphin massage and those who were not given Endorphin massage in Indramayu Regency. This research is a quasi experimental study using a post -test only with control group design. The samples in this study were 30 people consisted of 15 women in study group (all received endorphin massage) and 15 others in control group (not given endorphin massage) . The effect of endorphin massage on the amount of blood loss on stage four of normal delivery was analyzed using unpaired t-test. The results showed that there were significant differences in the mean of blood loss in the stage four of normal deliveries between respondents who received endorphin massage and those who were not given endorphin massage ( p = 0.000 ) . Researchers suggest that midwives give more emphasis on mother care particularly giving Endorphin massage because in reality there are many midwives who do not know the benefits of Endorphin massage to reduce the amount of blood loss at stage four of delivery.